NON-RHEUMATIC MYOCARDITIDES - N. A. Shostak; A. A. Klimenko; V. S. Shemenkova; T. K. Loginova (Klinicist)
Myocarditis is an inflammatory disease of the myocardium, which is caused by different factors, such as infectious, immune, chemical, physical, and allergic ones. The main cause of the disease is viral agents. In 1837, the term “myocarditis” was introduced in medical prac tice by J.F. Sobernheim who considered the presence of an infectious agent and inflammatory and vascular disorders in the myocardium to be the major signs of the disease. The specific symptoms of myocarditis cannot be identified therefore it is rather hard to determine the prevalence of the disease in the population. However, the association with a definite etiological factor (such as with prior infection and use of some drugs) and the presence of the symptoms of myocardial lesion (chest pain, dyspnea, rhythm and conduction disturbances) may sug gest an idea on the possible development of myocarditis. Laboratory studies show an elevation of cardiospecific enzymes and the signs of an inflammatory response. Endomyocardial biopsy (EMB) is the gold standard for the diagnosis of myocarditis to the present day. The diag nostic value of the method is limited by technical feasibilities, the skills of medical staff, and the development of possible complications. Gadolinium magnetic resonance imaging that can visualize myocardial inflammatory foci may be used as an alternative to EMB. The de veloped criteria are of definite diagnostic value; however, the problems in making diagnosis and differential diagnosis remain unsolved. There are no specific myocarditis treatment methods and regimens. Symptomatic therapy is most commonly used depending on the existing manifestations of myocarditis. The intake of nonsteroidal antiinflammatory drugs and glucocorticosteroids is now a point open to question. It is necessary to remember about the prevention of infectious myocarditis and the sanitization of existing foci of infection in the body.